TOMIRA and Belabeliku.Com as MSME Product Marketing Media in Kulon Progo Regency - Muhammad Eko Atmojo; Awang Darumurti; Vindhi Putri Pratiwi; Helen Dian Fridayani (Universitas Teuku Umar, 2023)
The Kulon Progo Regency Government has implemented various policies to improve the economy and welfare of the community, including the Bela Beli Kulon Progo program and the Belabeliku.com marketplace. This study emphasizes the importance of government policies in empowering communities through MSMEs and the marketplace to enhance the economy and improve people's living conditions. To conduct this study, the descriptive qualitative research method was used. The People-Owned Stores Economic Development Policy (TOMIRA) is a special policy that has been developed by the local government in Kulon Progo Regency to revitalize and improve the welfare of Micro, Small, and Medium Enterprises (MSMEs) in the area. The policy involves collaborating with modern stores to safeguard local products and traditional markets from the capitalist system that exists in Indonesia. The government's commitment to preserving traditional markets and local products can be seen in the Kulon Progo Regency Regional Regulation Number 11 of 2011 on the Protection and Empowerment of Traditional Markets and the Structure of Shopping Centers and Modern Stores. The implementation of this policy began in 2014 and continues to this day, with approximately 19 TOMIRA in Kulon Progo Regency partnering with modern stores the government's collaboration with modern shops involves marketing, provision of business locations, and acceptance of MSME supply from big businesses. The TOMIRA policy is an important step in improving the economic growth and welfare of the region, and it sets an example for other local governments to prioritize innovation and prioritize MSMEs.